International Society for Peritoneal Dialysis Nurse Liaison Committee: perspectives in peritoneal dialysis. (2nd November 2019) - Hurst, Helen; Chow, Josephine; Bowes, Elaine; Figueiredo, Ana E; Brunier, Gillian; Hiramatsu, Miki; Walker, Rachael; Neumann, Joanna Lee; Ngaruiya, Grace Wanjiku
Abstract : Dr Helen Hurst and colleagues introduce the work of the International Society for Peritoneal Dialysis Nurse Liaison Committee, discussing international collaborations aimed at improving outcomes for patients on peritoneal dialysis and some key areas of work.